The nonlinear effect of financial openness on carbon emission intensity––evidence from 144 countries - Zhang, Zhe; Ding, Shengzhen; Li, Jing (Frontiers in Environmental Science, 2025)
Financial globalization is one of the defining elements of the modern world, and climate change is a common challenge faced by governments. Understanding the relationship between these two phenomena can help countries implement strategies of financial openness and pursue sustainable development. This paper employs two-way fixed-effects and mediation models to analyze the relationship between financial globalization and climate change using annual panel data from 144 countries for the period 2000 to 2001. The findings are as follows. (1) There is an inverted U-shaped nonlinear relationship between a country’s financial openness and its carbon emission intensity. A low level of financial openness tends to attract foreign capital into industrial projects reliant on fossil fuels, thereby increasing carbon emission intensity. However, once financial globalization reaches a certain threshold, a higher share of foreign capital is invested in renewable energy, resulting in a negative marginal impact on carbon emission intensity. (2) The mechanism tests show that financial globalization has an inverted U-shaped nonlinear relationship with carbon emission intensity through its effects on energy efficiency and the share of renewable energy, while it could also reduce carbon emission intensity by promoting technological advancements. (3) An increase in a country’s financial openness not only impacts its own carbon emission intensity,but also it has a nonlinear spatial spillover effect of initially promoting and then inhibiting on the carbon emission intensity of neighboring countries. These findings suggest that financial globalization, if managed strategically, can contribute to both economic growth and environmental sustainability, highlighting the potential for policy interventions that encourage clean energy investment and technological innovation.